ПОВЫШЕНИЕ ЭФФЕКТИВНОСТИ ДУГОВОЙ СОСТАВЛЯЮЩЕЙ ЛАЗЕРНО-ДУГОВОГО РАЗРЯДА - Бушма , А.И.; Сидорец , В.Н.; Бойи , У. (Інститут електродинаміки НАН України, Київ, 2016)
Volt-ampere characteristics of the laser-arc discharge for different rates of absorption of laser radiation of the base metal have been corrected by taking into account in the energy conservation law the additional input power, which determines by interaction of electric arc plasma with the laser radiation. It is shown that along with a increasing the efficiency of the laser component of the heat source, also increases the efficiency of the arc component due to a significant increasing the absorption coefficient of the laser radiation during the transition of the metal in the liquid state. To determine the temperature dependence of the absorption coefficient of laser radiation by metallic materials the metal under study was considered within the nearly free electron model. In this case, according to the Drude-Zener theory the absorption coefficient is mainly determined by the specific resistance of the metal. References 5, figures 4.